2019
DOI: 10.1093/cid/ciz653
|View full text |Cite
|
Sign up to set email alerts
|

First-in-Human Randomized Study to Assess the Safety and Immunogenicity of an Investigational Respiratory Syncytial Virus (RSV) Vaccine Based on Chimpanzee-Adenovirus-155 Viral Vector–Expressing RSV Fusion, Nucleocapsid, and Antitermination Viral Proteins in Healthy Adults

Abstract: Background Respiratory syncytial virus (RSV) disease is a major cause of infant morbidity and mortality. This Phase I, randomized, observer-blind, placebo- and active-controlled study evaluated an investigational vaccine against RSV (ChAd155-RSV) using the viral vector chimpanzee-adenovirus-155, encoding RSV fusion (F), nucleocapsid, and transcription antitermination proteins. Methods Healthy 18–45-year-old adults received Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 25 publications
0
44
0
Order By: Relevance
“…Importantly, we demonstrate here that the vectored vaccine is compatible with the licensed vaccine in a simulated PEP in NHP, since it strongly boosts VNA titers induced by a previous vaccination with RABIPUR. In addition, a homologous boost with ChAd155-RG one year after priming was highly effective in all animals, despite the presence of anti-vector nAb titers similar to those detected in humans with pre-existing cross-reactive immunity to ChAd155 [ 45 ]. On the basis of genetic distance and serological cross-reactivity, the Lyssavirus genus has been subdivided into three broad phylogroups I-III.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we demonstrate here that the vectored vaccine is compatible with the licensed vaccine in a simulated PEP in NHP, since it strongly boosts VNA titers induced by a previous vaccination with RABIPUR. In addition, a homologous boost with ChAd155-RG one year after priming was highly effective in all animals, despite the presence of anti-vector nAb titers similar to those detected in humans with pre-existing cross-reactive immunity to ChAd155 [ 45 ]. On the basis of genetic distance and serological cross-reactivity, the Lyssavirus genus has been subdivided into three broad phylogroups I-III.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their lower seroprevalence and thus decreased vector neutralization in humans as compared to human Ad5, chimpanzee Ad (ChAd) vectors represent an attractive vaccine platform (3)(4)(5). ChAdvectored candidate vaccines against infectious diseases such as malaria, Ebola, and RSV have shown favorable immunogenicity and tolerability in humans (6)(7)(8)(9)(10)(11). These vaccines drive robust intracellular antigen expression, thus promoting a CD8 + T-cellbiased response, but were also shown to induce antigen-specific CD4 + T-cell responses and antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…These properties have guided the selection of this platform for several vaccine candidates with a ChAd serotype 155 [ChAd155 (12,13)] backbone. These vaccines include the pediatric RSV vaccine ChAd155-RSV (7) currently in Phase II development (NCT02927873), as well as the rabies vaccine ChAd155-RG and the therapeutic hepatitis B vaccine ChAd155-hIi-HBV, both in Phase I development (NCT04019444 and NCT03866187, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Sequencing of viral samples suggested that modifications were generated post-vaccination in a number of subjects that promoted a reduction in the expression of the F protein correlating with lower neutralizing antibodies in those individuals ( 27 ). A recently developed vaccine composed of a chimpanzee adenovirus viral vector expressing the RSV F, N, and M2-1 proteins (ChAd155-RSV) induced robust neutralizing antibody titers and interferon gamma (IFNγ)-secreting T cells compared to placebo controls ( 28 ). ReiThera Srl developed a similar vaccine using a chimpanzee adenovirus (PanAd3) viral vector expressing the RSV F, N, and M2-1 proteins in combination with a modified vaccinia virus Ankara (MVA).…”
Section: Rsv Vaccine Modalities and Lessons From The Host Immune Respmentioning
confidence: 99%